1984
DOI: 10.1507/endocrj1954.31.165
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic release of thyrotropin in response to thyrotropin-releasing hormon (TRH) from rat anterior pituitary cells in vitro: Possible dependence on protein synthesis.

Abstract: Mechanisms related to the biphasic release of TSH were studied using primary cultured cells of the rat anterior pituitary gland on micro-carrier beads in a superfusion system. Release of TSH in response to continuous exposure to TRH exhibited a biphasic pattern ; the first phase was characterized by a rapid, transient and high-rate release (phase I) and the second phase by a chronic and low-rate release (phase II). The shift of the release from phase I to phase II occurred by treatment with TRH at concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In mammalian studies, TRH stimulation of thyrotropin release [7,31] and prolactin release [2,26] have been described as biphasic, consisting of a very rapid initial phase of hormone secretion, followed by a plateau of elevated secretion. It has been suggested that different intracellular mechanisms are responsible for the two phases of TRH-induced stimulation [2,26,34]. Interestingly, studies with rat thyrotropes [2] and GH3 tumor cells [34] indicate that the second phase of the response to TRH is dependent on protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian studies, TRH stimulation of thyrotropin release [7,31] and prolactin release [2,26] have been described as biphasic, consisting of a very rapid initial phase of hormone secretion, followed by a plateau of elevated secretion. It has been suggested that different intracellular mechanisms are responsible for the two phases of TRH-induced stimulation [2,26,34]. Interestingly, studies with rat thyrotropes [2] and GH3 tumor cells [34] indicate that the second phase of the response to TRH is dependent on protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that different intracellular mechanisms are responsible for the two phases of TRH-induced stimulation [2,26,34]. Interestingly, studies with rat thyrotropes [2] and GH3 tumor cells [34] indicate that the second phase of the response to TRH is dependent on protein synthesis. The melanotropes of white-background adapted Xenopus are known to have an extremely low level of biosynthetic activity [19,24,48].…”
Section: Discussionmentioning
confidence: 99%
“…PRL, GH, and TSH in the serum were assayed by radioimmunoassay using the antisera provided by the NIADDK Rat Pituitary Hormone Distribution Program, and the results were expressed in terms of NIAMDD-rat PRL-RP-2, NIAMDD-rat GH-RP-1, and NIADDK-rat TSH RP-2, respectively, according to the method described earlier (8,9). Thyroxine (T,) and triiodothyronine (T3) in the serum were assayed using kits (Mallinckrodt Inc., St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%